2013
DOI: 10.1007/s13277-013-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 inhibits osteosarcoma cell proliferation by targeting Cyr61

Abstract: Increasing evidence indicates that microRNAs (miRNAs) participate in almost every step of cellular processes and are often aberrantly expressed in human cancer. Therefore, the discovery of miRNAs may provide a new and powerful tool for understanding the mechanism and treatment of carcinogenesis. The aim of this study was to investigate the functional significance of miR-100 and to identify its possible target genes in osteosarcoma (OS) cells. Here, we found that expression level of miR-100 was significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…Because of the advancement of its treatment, including surgery and multi‐agent chemotherapy, the 5‐year survival rate in patients with primary osteosarcoma has improved over the past several decades 5, 6, 7, 8. However, the survival rate for this tumour remains low 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the advancement of its treatment, including surgery and multi‐agent chemotherapy, the 5‐year survival rate in patients with primary osteosarcoma has improved over the past several decades 5, 6, 7, 8. However, the survival rate for this tumour remains low 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that miR-100 was significantly downregulated in osteosarcoma tissues and inhibited osteosarcoma cell proliferation by targeting Cyr61. 16 However, the role and mechanism of miR-100 in regulating tumorigenesis are still to be further elucidated. In this study, we will investigate (1) what is the role of miR-100 in osteosarcoma cell growth, migration, and invasion; (2) what is the direct target of miR-100 that is associated with cancer development; (3) whether there is a relationship between miR-100 and its direct target; and (4) whether miR-100 and its target are responsible for the resistance to cisplatin treatment in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression of the CYR61 gene is regulated by TP53, miRNA-22 and miRNA-100 as well as through activation of the PI3K/Akt signaling [10,18,19]. It is interesting to note that degradome products of this matricellular protein may modulate the pathological angiogenesis in the retina [20].…”
Section: Experimental Researchmentioning
confidence: 99%
“…Adipose tissue growth is a center of obesity, is tightly associated with apoptosis and the cell proliferation processes, and is controlled by different interconnected regulatory factors and enzymes [1,6,8]. Special interest should be given to key regulatory factors and enzymes, which control cell growth and survival, especially GADD45A, PLAGL1, CYR61, PPP1R15A, TFPI2, HSPA6, and ITGA5 [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation